Algebra's Ripple Effect: How Enthusiasm for Algebra Shapes Students' Overall Attitudes Toward Mathematics - Ajai, John Tyavbee; Sanda, Hauwa; Abur, Cletus Terhemba (EDUPEDIA PUBLISHER, 2024)
Purpose: This study investigates the